ON THE MILNOR MONODROMY OF THE IRREDUCIBLE COMPLEX REFLECTION ARRANGEMENTS. (8th November 2017) - Dimca, Alexandru
Abstract : Using recent results by Măcinic, Papadima and Popescu, and a refinement of an older construction of ours, we determine the monodromy action on H^1(F(G), C), where F(G) denotes the Milnor fiber of a hyperplane arrangement associated to an irreducible complex reflection group G .